2016
DOI: 10.3892/or.2016.5302
|View full text |Cite
|
Sign up to set email alerts
|

DEK protein overexpression predicts poor prognosis in pancreatic ductal adenocarcinoma

Abstract: DEK, a transcription factor, is involved in mRNA splicing, transcriptional control, cell division and differentiation. Recent studies suggest that DEK overexpression can promote tumorigenesis in a wide range of cancer cell types. However, little is known concerning the status of DEK in pancreatic ductal adenocarcinoma (PDAC). Based on the microarray data from Gene Expression Omnibus (GEO), the expression levels of DEK mRNA in PDAC tissues were significantly higher than levels in the adjacent non-tumor tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Multivariate survival analysis confirmed DEK overexpression as an independent predictive factor of poor survival in ESCC, alongside TNM stage and lymph node metastasis (Table III). The association of DEK overexpression with disease-free survival or survival rates was consistent with other studies which reported that increased DEK expression was clearly correlated with poor prognosis in other solid tumors [7,31,32]. Sun et al demonstrated that patients with high DEK expression had a lower overall survival rate than those with low DEK expression [31].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Multivariate survival analysis confirmed DEK overexpression as an independent predictive factor of poor survival in ESCC, alongside TNM stage and lymph node metastasis (Table III). The association of DEK overexpression with disease-free survival or survival rates was consistent with other studies which reported that increased DEK expression was clearly correlated with poor prognosis in other solid tumors [7,31,32]. Sun et al demonstrated that patients with high DEK expression had a lower overall survival rate than those with low DEK expression [31].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the rate of DEK overexpression was considerably increased in poorly differentiated esophageal cancer (85.1%) compared with moderately and well-differentiated cancers (39.7%, p < 0.001). Several studies have also reported that DEK overexpression was significantly related to clinical prognostic parameters [23,[31][32][33]. Liu et al reported that DEK expression level is considerably higher in invasive ductal breast cancer compared with normal breast tissue and associated with proliferation (Ki-67 levels) and histological grade, indicating that DEK might potentially be an indicator for early detection and prognosis [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DEK was originally discovered as part of the fusion protein DEK-NUP214 (i.e. DEK-CAN), a result of a t(6;9) chromosome translocation in a subset of patients with acute myelogenous leukemia [14*], and as an oncoprotein in various neoplasms including melanoma [57*], breast cancer [8], glioblastoma [9], hepatocellular carcinoma [10, 11*], retinoblastoma [12, 13], gastric adenocarcinoma [14*], non-small cell lung cancer [15*], pancreatic ductal adenocarcinoma [16*], and bladder cancer [17]. DEK was found to be a regulator of hematopoiesis controlling HSC and HPC numbers/fate decision [18, 19].…”
Section: Introductionmentioning
confidence: 99%